2020
DOI: 10.1167/iovs.61.3.35
|View full text |Cite
|
Sign up to set email alerts
|

Automated Evaluation of Parapapillary Choroidal Microvasculature in Ischemic Optic Neuropathy and Open Angle Glaucoma

Abstract: Citation: Aghsaei Fard M, Salabati M, Mahmoudzadeh R, et al. Automated evaluation of parapapillary choroidal microvasculature in ischemic optic neuropathy and open angle glaucoma. Invest Ophthalmol Vis Sci. 2020;61(3):35. https://doi.org/10.1167/iovs.61.3.35 PURPOSE.To determine whether parapapillary choroidal microvasculature (PPCMv) density as measured by optical coherence tomography angiography differs between nonarteritic anterior ischemic optic neuropathy (NAION) and primary open angle glaucoma (POAG). ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…However, despite the discrepancy in CMvD characteristics between NAION and NTG eyes, there was no significant difference in the choroidal VD within the β-PPA between them. Our results differed from those of Fard et al, who reported that choroidal VD was significantly reduced in eyes with primary open-angle glaucoma compared to eyes with NAION but that it did not differ significantly between NAION and healthy control eyes 29 . This discrepancy may be explained by differences in study design and methodology for measuring choroidal VD.…”
Section: Discussioncontrasting
confidence: 99%
“…However, despite the discrepancy in CMvD characteristics between NAION and NTG eyes, there was no significant difference in the choroidal VD within the β-PPA between them. Our results differed from those of Fard et al, who reported that choroidal VD was significantly reduced in eyes with primary open-angle glaucoma compared to eyes with NAION but that it did not differ significantly between NAION and healthy control eyes 29 . This discrepancy may be explained by differences in study design and methodology for measuring choroidal VD.…”
Section: Discussioncontrasting
confidence: 99%
“… 41 43 In the choroid, a different involvement pattern has been questioned. 44 Our hypothesis may conceptually connect the retina and the choroid.…”
Section: Discussionmentioning
confidence: 90%
“…To avoid the shadowing effect of neurosensory detachment that affects the OCTA flow signal in the choriocapillaris, we applied the CCD of a fellow eye for analysis [ 12 ]. Previously developed and validated custom MATLAB software (MathWorks, Inc., Natick, MA, USA) was used to process and analyze these OCTA images or en face images [ 13 , 14 ]. In brief, the density algorithm included three key steps: constructing the binary location of large retinal vessel shadows; capillary segmentation using the modified Otsu algorithm; and calculating the density values of the choroidal vasculature.…”
Section: Methodsmentioning
confidence: 99%